Cognitive-pragmatic functions of mitigation in therapeutic conversations emphasizing rapport management - Cheng, Lulu; Mao, Haoran; Zhang, Ting (Frontiers in Psychology, 2023)
Based on conversations between 15 clients and 5 therapists in the context of daily treatment, this study investigated therapist-client linguistic mitigation in a natural setting. The study found that (1) the therapists and clients mainly used three major types of mitigation, among which illocutionary mitigation and propositional mitigation were employed more frequently. Furthermore, direct dissuasion and disclaimers, as subtypes of mitigators, were the most regularly employed by therapists and clients, respectively. (2) Through cognitive-pragmatic interpretation under rapport management theory, it was found that mitigation in the therapist-client conversations mainly performed cognitive-pragmatic functions in giving the means to preserve positive face, maintaining social rights and concentrating on interactive goals, which were interpenetrated with each other in therapeutic conversations. (3) This study proposed that three cognitive-pragmatic functions jointly devoted to a rapport in therapeutic relationship to reduce therapeutic risk of conflicts.